Rescue of adult hippocampal neurogenesis in a mouse model of HIV neurologic disease - Myoung-Hwa Lee; Tongguang Wang; Mi-Hyeon Jang; Joseph Steiner; Norman Haughey; Guo-li Ming; Hongjun Song; Avindra Nath; Arun Venkatesan (Neurobiology of Disease, 2011)
The prevalence of central nervous system (CNS) neurologic dysfunction associated with human immunodeficiency virus (HIV) infection continues to increase, despite the use of antiretroviral therapy. Previous work has focused on the deleterious effects of HIV on mature neurons and on development of neuroprotective strategies, which have consistently failed to show a meaningful clinical benefit. It is now well established that new neurons are continuously generated in discrete regions in the adult mammalian brain, and accumulating evidence supports important roles for these neurons in specific cognitive functions. In a transgenic mouse model of HIV neurologic disease with glial expression of the HIV envelope protein gp120, we demonstrate a significant reduction in proliferation of hippocampal neural progenitors in the dentate gyrus of adult animals, resulting in a dramatic decrease in the number of newborn neurons in the adult brain. We identify amplifying neural progenitor cells (ANPs) as the first class of progenitors affected by gp120, and we also demonstrate that newly generated neurons exhibit aberrant dendritic development. Furthermore, voluntary exercise and treatment with a selective serotonin reuptake inhibitor increase the ANP population and rescue the observed deficits in gp120 transgenic mice. Thus, during HIV infection, the envelope protein gp120 may potently inhibit adult hippocampal neurogenesis, and neurorestorative approaches may be effective in ameliorating these effects. Our study has significant implications for the development of novel therapeutic approaches for HIV-infected individuals with neurologic dysfunction and may be applicable to other neurodegenerative diseases in which hippocampal neurogenesis is impaired.